Spawning and nursery areas of Decapterus macarellus: siting pelagic fisheries marine protected area (MPA) in the Sulawesi Sea, Indonesia - Amehr Hakim; Amehr Hakim; Budy Wiryawan; Budy Wiryawan; Ari Purbayanto; Am Azbas Taurusman; Firdaus Agung; Charles P. H. Simanjuntak; Prayekti Ningtias; Rian Prasetia; Tasrif Kartawijaya; Noviar Andayani; et al. (Frontiers in Marine Science)
IntroductionIdentifying spawning and nursery areas for exploited fish stocks is crucial for sustainable fisheries management, as these areas support fish reproduction and early development necessary for maintaining healthy fish populations. The mackerel scad, Decapterus macarellus, is a valuable species in Indonesia, playing a crucial role in the livelihoods of coastal communities and the national fishing industry. MethodsThis study aims to identify the spawning and nursery areas of D. macarellus in the Sulawesi Sea, specifically within Indonesia's Fisheries Management Area (FMA) 716. Field sampling was conducted at 25 sites using bongo net tows to collect D. macarellus larval specimens. Hydro-oceanographic conditions were measured, and larval ages were estimated through otolith analysis. Based on these data, trajectory models were developed to assess the D. macarellus spawning and nursery habitats within the Sulawesi Sea. ResultsResults indicate that spawning primarily occurs on the northern and western sides of Sangihe and Siau Islands. Nursery areas were identified in the southern Sulawesi Sea and Maluku Sea, where high zooplankton abundance supports juvenile growth. DiscussionOur findings highlight environmental conditions and critical habitats for D. macarellus, providing insights into spatial patterns of its spawning and nursery activities. The study underscores the need for pelagic fisheries marine protected area (MPA) to safeguard these critical habitats, ensuring sustainable fisheries amid increasing exploitation pressures. These findings provide a scientific basis for spatial management strategies, supporting Indonesia’s national MPA targets while offering a replicable framework for pelagic habitat conservation in other regions.